Optimalisasi Sistem Bisnis UMKM DIMSUM eya di Pangandaran: Analisis Masalah dan Solusi - Nurul Mardhiah Sitio; Linda Kurniawati; Luthfi Thirafi; Farisadri Fauzan (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
Micro, small and medium-sized enterprises (MSMEs) have the potential to generate new jobs, offer diverse economic services to society, and contribute to accelerating national growth and stability. Of course, MSMEs are a very important sector of the national economy that can affect the lives of people in general.One of the objectives of this research is to find solutions to the problems found in the business information system of Dim Sumeya MSMEs in Pangandaran. Furthermore, data collection techniques are applied through observation and interview stages. This study was carried out by applying descriptive qualitative techniques which include analysis, summary of phenomena, as well as direct depiction of phenomena from data obtained through observations and interviews. The study collected information through interviews with the owner of Dim Sumeya. The results indicated that Dim Sumeya has not maximised its digital financial transaction recording and still does it manually. As a result, the author recommends the use of the BukuWarung application. Through this application, Dim Sumeya can support their micro, small, and medium enterprises (MSMEs) in the management of the financial system, thus minimising the risks associated with using the application.